Shea Butter Wax Application to Enhance the Storability of Mill Tomato and Bell Green Pepper Fruits - Daud Waahu Nuhu, Daari Adams, Issah Sohanwine Abdulai, Adams abdul-Rahaman, Nasiru Alhassan (Journal of Aridland Agriculture, 2015)
The consumption of perishable fruits and vegetables forms an essential part of nutrition through the provision of nutrients for growth and good health. However, farmers, marketers, and consumers encounter several challenges regarding the keeping of fresh commodities such as Mill tomato and Bell green pepper fruits to increase the shelf life due to quick degeneration and decomposition of the produce at storage. The need for the consumption of fresh fruits and vegetables increased across the world which resulted in the need for storage of these perishables. The objective of the study was to determine the effects of shear butter as a wax on the shelf life of mill tomato and bell green pepper fruits in ambient temperature and charcoal evaporative cooler (CEC), cultivated in communities in the Wa Municipality of the Upper West Region of Ghana. The results obtained on percentage weight loss of fresh green pepper coated with shea butter stored in charcoal evaporative cooler and ambient temperature monitored for an experimental period of seven (7) days showed that, the least percentage weight loss for green pepper was found with uncoated fruits sample stored at ambient with 1.37% but the highest was found with coated in evaporative cooler. However, the least weight loss for tomato fruit was found in coated tomatoes with 1.07% compared with coated sample at ambient with 2.78%. The experiment was terminated on day 7 with uncoated green pepper with the highest value of 6 compared with the uncoated sample in evaporative cooler with 3.7(Figure 3). The uncoated tomato samples showed that fruits in evaporative cooler were decaying more than those at ambient with the highest value of 5. The least glossiness was found in both uncoated fruits samples in the two conditions but the highest was shown by fruits sample coated and stored in evaporative cooler. Based on the scores produced, it was clear that the sample coated in cooler was more preferred.